Animal Agriculture and Global Food Supply - Bradford, Eric; Baldwin, R. Lee; Blackburn, Harvey; Cassman, Kenneth G.; Crosson, Pierre R.; Delgado, Christopher L.; Fadel, James G.; Fitzhugh, Henry A.; Gill, Margaret; Oltjen, James W.; Rosegrant, Mark W.; Vavra, Martin; et al. (Council for Agricultural Science and Technology (CAST), 1999)
A task force of 13 scientists discusses projected demand for human food and the importance of animal agriculture in meeting these needs.
Keywords: Animal Agriculture; Globe; Food Supply